Preserving Privacy when Querying OMOP CDM Databases...European Federation for Medical Informatics (EFMI) Special Topic Conference (STC), September 7–8, 2022, Cardiff, Wales - ALMEIDA, Joao Rafael; BARRACA, Joao Paulo; OLIVEIRA, José Luís (Studies in Health Technology & Informatics, 2022)
Anonymisation is currently one of the biggest challenges when sharing sensitive personal information. Its importance depends largely on the application domain, but when dealing with health information, this becomes a more serious issue. A simpler approach to avoid inadequate disclosure is to ensure that all data that can be associated directly with an individual is removed from the original dataset. However, some studies have shown that simple anonymisation procedures can sometimes be reverted using specific patients' characteristics. In this work, we propose a secure architecture to share information from distributed databases without compromising the subjects' privacy. The anonymiser system was validated using the OMOP CDM data schema, which is widely adopted in observational research studies.